APLIKASI GRAPH COLORING PADA PENJADWALAN PERKULIAHAN DI FAKULTAS SAINS DAN TEKNOLOGI UIN SUNAN AMPEL SURABAYA - Devi Saidatuz Zaenab; Deasy Alfiah Adyanti; Aris Fanani; Nurissaidah Ulinnuha (Jurnal Matematika MANTIK, 2016)
In the academic environment there are various problems, one of problem is scheduling of courses at the university level. These problems are affected by the allocation of time (Conformity of SKS with each course), the availability of classrooms, and many study program. In the study preparation lecture schedules in this time, the parameters used, among others: second semester students in each Study Program, Number of Study Program, availability of classrooms, Lectures, number of credits a day of each study program at the Faculty of Science and Technology. This research is aimed as an alternative in formulating scheduling system when the faculty there is an imbalance between the lecture hall, many Study Program, and the number of credits taken each Study Program. Based on the analysis of Graph Coloring and Edge Coloring at case of scheduling Study Program Faculty of Science and Technology State Islamic University Sunan Ampel Surabaya, which has 6 Programs and 5 lecture room with three simulated combinations of input data, obtained scheduling unchanged (consistent) and results scheduling does not overlap / collision, both in the lecture room, and the time of the lecture.